Water tariff setting and its welfare implications evidence from cities in the People Republic of China. - Jiang, Yi (Economics working papers.)
First, the authors show that peer cities average water tariffs have a significant influence on a city tariff levels. The former is then used as an instrumental variable to correct the endogeneity bias in estimating water demand functions. Estimation of a translog multiproduct joint cost function reveals strong scale and scope economies in urban water supply. Comparing the equilibrium and actual tariffs, the study estimates a moderate welfare loss under first best pricing in the context of the People Republic of China.